Integrating Social Work Within Legal Clinics: An Inter-Professional Perspective to Address Social-Legal Needs - Lam, Alicia; Emery, Vanessa; Griffin, Renee; Saini, Michael (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2022)
This project is a key demonstration of the benefits of social workers practising alongside lawyers within a legal clinic. Inter-professional practice between lawyers and social workers responds holistically to the needs of individuals experiencing socio-legal issues by both addressing their legal issues while supporting their mental, emotional, and spiritual well-being and adjustment. We provide lessons learned based on a new initiative that integrates social work within a legal clinic as a means of providing opportunities to receive individualized support while addressing legal issues.